KONTRIBUSI PEMBELAJARAN APRESIASI PROSA FIKSI BERBASIS BUDAYA DALAM INTERNASIONALISASI BAHASA INDONESIA MAHASISWA IAIN TULUNGAGUNG - Muyassaroh, Muyassaroh (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura)
Education becomes an important aspect in the life of people and nation. Through this education, the character of students will be formed to contribute the development of Indonesian national identity. This value or character inculcation involves three important elements; family, school and community environment. For the in instilment of character in schools, it can be integrated in a learning process including character values to be grasped directly by students. One of ways the lecturer can do is by learning to appreciate fiction prose. Students will communicate intensely with various characters from the fiction prose they read, packaged interestingly to be studied. The learning fiction prose appreciation needs to be taught and developed based on culture because it is expected by studying culture, the students will grow in love with Indonesian national culture. In this course, students are asked to find cultural values in Indonesian fiction prose. By learning this value, love of national culture, especially Bahasa, is getting stronger. This is based on the spirit that a great nation is a nation that upholds its culture. Therefore, the use of fiction prose as a means of instilling a love of the Indonesian nation's culture has proven to be effective in the dignification and internationalization of Bahasa because its status as a national language and the language of the country must be upheld.